An SERS analytical protocol for characterizing native Japanese plant extracts. (19th February 2020) - Kato, Kana; Doherty, Brenda; Degano, Ilaria; Sabatini, Francesca; Miliani, Costanza; Romani, Aldo; Ito, Ken; Brunetti, Brunetto G.
Abstract: The identification of natural dyes in ancient textiles is a longstanding challenge for scientists; yet, the effort honours the skill and knowledge of master dyers by retracing traditional dyeing methods and assisting in conserving historical treasures for future generations. Here, the main constituents of selected native Japanese extracts from the roots of Lithospermum erythrorhizon and Scutellaria baicalensis, the barks of Phellodendron amurense and Morella rubra, the dried flower bud of Syzygium aromataticum, and the fruit of Terminalia chebula are determined by surface‐enhanced Raman spectroscopy following traditional Japanese extraction methods. The analytical amalgamation of data from SERS examinations on crude extracts and on subsequently refiltered and diluted extracts provides further effective and sensitive results for the combined identification of napthoquinones (shikonin and alkanin), alkaloid (berberine), polyhydroxyflavonoids (baicalin/baicalein, myricetin/myricitrin), diarylheptanoids, allylbenzene (eugenol), and tannins (gallic/ellagic acid). The comparison of results from this analytical protocol with those achieved by the more traditional chromatographic and mass spectrometric method provides and questions data regarding generally accepted marker components and enantioselective discriminations that serve to enrich the database of biological sources of colouring materials to be used in determining historically important Japanese colorants and dyestuffs. Abstract : In this work, the high sensitivity and selectivity of colloidal SERS has been applied to investigate six natural Japanese plant sources on aqueous extraction by traditional recipes. The collection of reference spectra by SERS methods on both the crude extracts and following a further sample dilution provides a simple yet effective SERS protocol leading to a more thorough interpretation of data.